Externalismus und Selbstkenntnis: die McKinsey-Paradoxie - Dierig, Simon (Zeitschrift für philosophische Forschung, 2018)
The most important argument for the incompatibility of semantic externalism and a priori self-knowledge is the so-called McKinsey paradox. In this essay, it is shown that the most familiar proposal for a dissolution of that paradox, viz, the one espoused by Crispin Wright, is unconvincing. - Second, an alternative solution of the McKinsey paradox is outlined. It relies on the claim that the standard justification for externalism, namely the one based on Hilary Putnam's and Tyler Burge's Twin Earth thought experiment, is not entirely a priori because it incorporates an account - of concept acquisition which cannot be known from the armchair.